Understanding Thermal Tolerance of Potential Fish in the changing climatic environment - Aftabuddin, Md; Roychowdhury, Prasun; Sarkar, U K (Indian Farming, 2017)
Future climate change variations will be threat for several fish species and there is need for identifying alternative species for sustainable production and livelihood of fisherman communities. Therefore, identification of tolerant species is essential and in this context CTmax of 14 fish species of different sizes and habitat (seasonal temperature) from natural resources and culture systems were assessed by the ICAR- Central Inland Fisheries Research Institute, Barrackpore under NICRA project. Both physical and biochemical approaches have importance to monitor thermal stress. Physical approaches are sufficient to monitor survivability but biochemical tools are better for assessment at initial stages of stress as it is reflected earlier at molecular level than physiologicalappearance.